History of special education - Rotatori, Anthony F.; Obiakor, Festus E.; Bakken, Jeffrey P. (Advances in special education ;, 2011)
This volume will examine the history of special education by categorical areas (e.g., Learning Disabilities, Mental Retardation, Autistic Spectrum Disorders). Each categorical area chapter will include an examination of: changing definitions, early pioneers in the field, major contributors and their theoretical ideas, changing educational and treatment practices, working with families, the use of technology, assessment practices and legislative acts specific to that categorical area. The volume will also include chapters on the changing philosophy related to educating students with exceptionalities as well as a detailed history of legal and legislation content concerned with special education. The volume will provide readers with a unique perspective on why special education is what it is today.